2017
DOI: 10.4236/me.2017.82009
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Systems Engineering Techniques on New Product Development: Results from Interview Research at Corning Incorporated

Abstract: In new product development (NPD) in the commercial (as opposed to military/aerospace) environment, many firms express confidence in the value of applying systems engineering (SE) techniques to the NPD process, even though there is little research to date that systematically evaluates the benefits of SE in the commercial setting. The goal of this paper is therefore to address this gap in the research by testing for SE impact across multiple projects, in this case within a single enterprise, namely Corning Incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In relation to the application of systems engineering (SE) techniques, F. Vanek, et al [14] studied the benefits that using SE techniques generate in new product development. The authors found a positive association between high performing projects and utilization of SE techniques, and they also found that projects with deficient performance were characterized by a lack of SE technique implementation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the application of systems engineering (SE) techniques, F. Vanek, et al [14] studied the benefits that using SE techniques generate in new product development. The authors found a positive association between high performing projects and utilization of SE techniques, and they also found that projects with deficient performance were characterized by a lack of SE technique implementation.…”
Section: Related Workmentioning
confidence: 99%
“…Systems Engineering is an engineering discipline that aims to tackle the growing complexity of sociotechnical systems; therefore, it studies the application of strategies to conceptualize, build, and operate engineered systems [16,17]. This approach has traditionally been used in the development of aerospace and defense related systems, but its implementation in civil and commercial applications has gained ground in recent years due to its demonstrated effectiveness in producing better performance outcomes [14]. This paper hopes to broaden systems engineering application to support the development of an IoT system that aims to improve packaging design and logistics operations.…”
Section: Using Mbse For Iot System Designmentioning
confidence: 99%
“…The extent of digitalization suggests that one of the key toolsets for re-gaining market positions may come from software industry, in which Systems Engineering (SE) has been applied extensively [5]. Due to specific mindset based on systems thinking, SE can manage complex systems and has been proved to improve project results in new product development [6,7]. It is a structured methodology, which mainly aims to meet the needs of stakeholders and satisfy their requirements throughout the product development processes [8].…”
Section: Introductionmentioning
confidence: 99%
“…(Falk & Muller, 2019) It has proven its effectiveness in New Product Development projects, resulting in improved product quality, increased budgetary effectiveness, faster time to market values and further developments in other aspects. (Vanek et al, 2017) Despite the facts that automotive industry has been facing with an immense technical revolution as well as new organizational challenges arise aiming to better meet the stakeholder needs, firms have barely applied this methodology so far. Although, an amount of studies concern imagined or realized effects of SE within the field, they mostly touch production cases or discuss the implementation on a theoretical basis (Dumitrescu et al, 2013;Gál et al, 2013;Fischer et al, 2020;Gyenge et al, 2021;Rabe et al, 2022).…”
Section: Introductionmentioning
confidence: 99%